(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Studies have shown that less coke is produced in the presence of catalysts supported on nickel-based carriers [12; pp. 359-372, 13; pp. 22]. If the metal is supported on a carrier with a high Lewis basicity, the production of char decreases.